Outcomes of total hip arthroplasty using dual mobility components in patients with a femoral neck fracture: a systematic review and meta-analysis. (July 2020) - You, Daniel; Sepehri, Aresh; Kooner, Sahil; Krzyzaniak, Halli; Johal, Herman; Duffy, Paul; Schneider, Prism; Powell, James
Abstract : Aims: Dislocation is the most common indication for further surgery following total hip arthroplasty (THA) when undertaken in patients with a femoral neck fracture. This study aimed to assess the complication rates of THA with dual mobility components (THA-DMC) following a femoral neck fracture and to compare outcomes between THA-DMC, conventional THA, and hemiarthroplasty (HA). Methods: We performed a systematic review of all English language articles on THA-DMC published between 2010 and 2019 in the MEDLINE, EMBASE, and Cochrane databases. After the application of rigorous inclusion and exclusion criteria, 23 studies dealing with patients who underwent treatment for a femoral neck fracture using THA-DMC were analyzed for the rate of dislocation. Secondary outcomes included reoperation, periprosthetic fracture, infection, mortality, and functional outcome. The review included 7, 189 patients with a mean age of 77.8 years (66.4 to 87.6) and a mean follow-up of 30.9 months (9.0 to 68.0). Results: THA-DMC was associated with a significantly lower dislocation rate compared with both THA (OR 0.26; 95% CI 0.08 to 0.79) and HA (odds ratio (OR) 0.27; 95% confidence interval (CI) 0.15 to 0.50). The rate of large articulations and of intraprosthetic dislocation was 1.5% (n = 105) and 0.04% (n = 3) respectively. Conclusion: THA-DMC when used in patients with a femoral neck fracture is associated with a lower dislocation rate compared with conventional arthroplasty options. There was no increase in the rates of other complication when THA-DMC was used. Future cost analysis and prospective, comparative studies are required to assess the potential benefit of using THA-DMC in these patients. Cite this article: Bone Joint J 2020;102-B(7):811–821.